VOCATIONAL AND TECHNOLOGICAL EDUCATION IN BRAZIL: HISTORICAL TRAJECTORY, PUBLIC POLICIES, AND PERSPECTIVES FOR REGIONAL DEVELOPMENT - Góes, Láudia Silva de Oliveira (Seven Editora, 2026)
This analyzes the historical trajectory of Vocational and Technological Education (VTE) in Brazil, from the Schools of Apprentices and Artisans (1909) to the present day, examining the public policies that shaped this educational field and their implications for regional development. Based on reference authors such as Frigotto, Ciavatta, Ramos, Saviani, Pacheco, Kuenzer, and Moraes, the study articulates the historical dimension of VTE with the contemporary challenges of social inclusion, professional qualification, and sustainability. The analysis shows that the structural duality between preparatory and vocational training remains a central obstacle to the consolidation of a comprehensive and emancipatory education. It is argued that overcoming this duality requires not only curricular and institutional reforms, but a profound reorientation of public policies, capable of articulating education, work, science, and culture as inseparable dimensions of national development. The study also highlights the relevance of the Federal Institutes of Education, Science and Technology as strategic agents of regional development, with emphasis on Northern Amazonia and the role of the Federal Institute of Amapá (IFAP) in training qualified human capital for emerging sectors, such as energy and oil.